2019
DOI: 10.3390/genes10100824
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Gene Inheritance Patterns on the Heterosis of Abdominal Fat Deposition in Chickens

Abstract: Heterosis, a phenomenon characterized by the superior performance of hybrid individuals relative to their parents, has been widely utilized in livestock and crop breeding, while the underlying genetic basis remains elusive in chickens. Here, we performed a reciprocal crossing experiment with broiler and layer chickens and conducted RNA sequencing on liver tissues for reciprocal crosses and their parental lines to identify inheritance patterns of gene expression. Our results showed that heterosis of the abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
5
15
0
Order By: Relevance
“…A previous study showed that high-parent dominance DEG are important in heterosis in Drosophila melanogaster and contribute specifically to BW heterosis (Wu et al, 2016). In chickens, heterosis of abdominal fat percentage was 69.28 to 154.71% in reciprocal crosses and highparent dominance accounted for approximately 50% of nonadditive genes in reciprocal crosses (Mai et al, 2019). A threshold of gene expression 1.25-fold change was used to classify inheritance categories in our study and previous studies (McManus et al, 2010;Gu et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
“…A previous study showed that high-parent dominance DEG are important in heterosis in Drosophila melanogaster and contribute specifically to BW heterosis (Wu et al, 2016). In chickens, heterosis of abdominal fat percentage was 69.28 to 154.71% in reciprocal crosses and highparent dominance accounted for approximately 50% of nonadditive genes in reciprocal crosses (Mai et al, 2019). A threshold of gene expression 1.25-fold change was used to classify inheritance categories in our study and previous studies (McManus et al, 2010;Gu et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
“…Pattern of differential expression of genes are potential mechanisms underlying heterosis ( Mai et al., 2019 ; Zhou et al., 2019 ). Antimullerian hormone primarily regresses the right oviduct of hens during development in addition to completely inhibiting its development in roosters ( Johnson et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pattern of enhancing dominance was more prevalent than suppressing dominance in most groups, indicating that up-regulated dominant events potentially play important roles in heterosis. Previous studies on body weight in Drosophila and gene expression modes in the liver of chickens have shown similar results (Mai et al, 2019). However, due to different cluster methods used, other studies have reported that additivity is the main gene expression pattern in embryonic chickens (Wu et al, 2016;Zhuo et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Studies on Camellia and coffee have indicated that the non-additive expression prevailed over other patterns ( Marie-Christine et al, 2015 ; Zhang et al, 2019 ). On the other hand, several studies have suggested that additivity is the predominant genetic pattern in maize, rice, and cotton ( Swanson-Wagner et al, 2006 ; Li et al, 2008 ; Rapp et al, 2009 ), while divergent outcomes suggest that additive or high parent-dominance is the major pattern in chickens ( Mai et al, 2019 ; Zhuo et al, 2019 ). Most previous studies have identified different inheritance patterns based on gene expression, and there is rarely a transcriptomic study that investigates AS event patterns, considering the association between AS and gene regulation at the post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%